2016
DOI: 10.1177/0020764016651459
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and discrimination experienced by people living with severe and persistent mental illness in assertive community treatment settings

Abstract: Discrimination was highly prevalent in everyday aspects of life. While healthcare professionals often tend to increase perceived stigma and discrimination, this was only experienced in interactions with general health professionals, while interactions with ACT team members decreased perceived stigma and increased positive discrimination. This indicates that healthcare professionals potentially have a significant role in reducing stigma and discrimination in mental health and that such an effect may be optimise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 45 publications
(66 reference statements)
2
27
0
12
Order By: Relevance
“…Out of all patients who were reachable, nearly 20% refused to participate. This is in agreement with Ventura et al, 17 where almost half their patients declined a simple psychiatric interview fearing to receive a diagnosis of a psychiatric disorder, because of public stigma, prejudice, and discrimination toward mentally ill patients, 29 , 30 which subsequently leads to under-recognition of major psychiatric disorders. Alternatively, one may postulate that simple reassurance and education about the disease’s benign nature and positive prognosis may minimize its negative effect and improve outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Out of all patients who were reachable, nearly 20% refused to participate. This is in agreement with Ventura et al, 17 where almost half their patients declined a simple psychiatric interview fearing to receive a diagnosis of a psychiatric disorder, because of public stigma, prejudice, and discrimination toward mentally ill patients, 29 , 30 which subsequently leads to under-recognition of major psychiatric disorders. Alternatively, one may postulate that simple reassurance and education about the disease’s benign nature and positive prognosis may minimize its negative effect and improve outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Stigma is burdensome, affecting people living with SMI and their family members and hindering both recovery and rehabilitation (Koschorke et al, ; Lam, Lam, Lam, & Ku, ; Ye et al, ). Negative societal attitudes and stigma are major obstacles to the improvement of quality of life for people living with SMI (Koschorke et al, ; Lam et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Different mental health conditions are associated with differing levels of stigma, with the stigmatization of people living with SMI found to be significantly higher than that of depression (Lam et al, ). In Australia, while interactions with general health professionals tend to increase perceived stigma and discrimination, interactions with assertive community team members decreased perceived stigma and reduced negative discrimination (Ye et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, QoL research of people suffering from schizophrenia has been revealed as a predictor of treatment outcomes and de-institutionalization (Karow et Karow et al 2007). In addition, the patients' estimation of their QoL may differ significantly from the objective assessment (Hayhurst et al 2014) and is strongly related to stigma (Ye et al 2016).…”
Section: Introductionmentioning
confidence: 99%